The BRCA1 Ubiquitin ligase function sets a new trend for remodelling in DNA repair - Densham, Ruth M. (Nucleus, 2016)
The protein product of the breast and ovarian cancer gene, BRCA1, is part of an obligate heterodimer with BARD1. Together these RING bearing proteins act as an E3 ubiquitin ligase. Several functions have been attributed to BRCA1 that contribute to genome integrity but which of these, if any, require this enzymatic function was unclear. Here we review recent studies clarifying the role of BRCA1 E3 ubiquitin ligase in DNA repair. Perhaps the most surprising finding is the narrow range of BRCA1 functions this activity relates to. Remarkably ligase activity promotes chromatin remodelling and 53BP1 positioning through the remodeller SMARCAD1, but the activity is dispensable for the cellular survival in response to cisplatin or replication stressing agents. Implications for therapy response and tumor susceptibility are discussed.